International Legal Protection For Climate Refugees: Where Lies The Haven For The Maldivian People? - Dolla, Simran (Journal of Sustainable Development Law and Policy, 2025)
Climate change and sea level rise are not just mere words for the Maldivian people; they are a grim reality that is consuming their nation. Sea level rise presents one of the gravest dangers for the Maldives because of its already low-lying characteristics. As the levels continue to rise, the nation is sinking into extinction. Some 300,000 people of the Maldives are on the brink of losing their homes and becoming climate change refugees. The existing international laws are not only ill-equipped to provide protections or the much-needed relief, they also make no mention of climate change refugees. Therefore, as the Maldivians await the result of the 2015 Paris Convention whose purpose is to achieve a binding universal agreement on climate change, they continue to face numerous human rights violations. Additionally, the loss of a nation does not only mean the loss of a home, it also means the loss of sovereignty at the international level. However, at the present time, finding a safe haven for its people is at the top of the Maldives agenda. The former president of the Maldives, Mohamed Nasheed, fought vigorously to bring the issue of sea level rise and climate change to the forefront. Knowing that such a day where he would have to move his people was not far in the distance, he also made plans to relocate. India and Australia have both been considered possible new homes; however, are both countries willing to take in such a large infiltration of refugees? What are the repercussions of moving to these countries? Would an artificial island possibly be the home the Maldivians are looking for? This article examines the options the Maldives has for relocation and why perhaps an artificial island may be a better solution.